Design of Web-Based Financial and Product Management System for Onemens Leather Admin Using the Agile Method - Denty Nirwana Bintang; Jovanca Blesshery Sinaga; Lutfi Riani; Afnan Zahra; Muhammad Nasir; Aditya Wicaksono (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This research aims to design and develop a web-based financial and product management system for Onemens Leather to address issues related to manual data management, which often leads to inefficiencies and errors in record-keeping. The system development employs the Agile Development methodology, which supports a flexible and adaptive software development process in response to user needs. The system is built using PHP programming language with the Laravel framework, and MySQL as the database management system. The outcome of this research is an interactive website providing key features such as a business performance dashboard, real-time product stock management, transaction recording, and automatic and structured reporting of inventory and financial data. The implementation of this system has proven to improve operational efficiency, accelerate data entry and reporting processes, enhance data accuracy, and support faster, more precise decision-making based on reliable data.